The young Joseph Banks: naturalist explorer and scientist, 1766–1772. (3rd July 2019) - Agnarsdóttir, Anna
ABSTRACT: As a young man Joseph Banks (1743–1820), a wealthy landowner, decided to devote his life to natural history. He became one of the best-known naturalist explorers of the eighteenth century. During his twenties, from 1766 to 1772, he went on three voyages of exploration: to Labrador and Newfoundland in 1766, on the Endeavour circumnavigation with James Cook in 1768–71 and, finally, in 1772, he led the first British scientific expedition to Iceland. It was these expeditions, undertaken as a young man, which shaped his life. From them he gained fame, becoming one of the country's most powerful and leading naturalists. This article also discusses the question of whether he was a scientist? He certainly believed himself to be one and according to the standards of the eighteenth century he was one, and people must be judged by the standard of their age. In the modern sense of the word, without a university degree and with negligible publications in his lifetime, he was not one. His eventual strength lay in his influential position as President of the Royal Society, a friend of George III and a privy councillor, allowing him to organise new voyages of discovery and send botanists on missions to collect the world's flora.